Pengaruh Kualitas Pelayanan dan Promosi terhadap Keputusan Pembelian Konsumen di Indomaret Buana Raya Padang Sambian Denpasar Bali (Jurnal Simki Economic, 2024)
This research aims to find out how much influence service quality and promotion have on consumer purchasing decisions at Indomaret Buana Raya Padang Sambian Denpasar Bali. This research used 44 respondents as research samples using SPSS 2024. The method used in this research was multiple linear regression analysis with a quantitative approach. The instrument used in this research was a questionnaire with a total of 26 statements consisting of 2 statements from each indicator variable. Based on the results of data analysis, a simple linear regression equation was obtained from the results of hypothesis testing, it was found that the research results showed that the service quality (x1) and promotion (x2) variables had a calculated f of >281.195 and a sig value of 0.001 and an f table value of f table and sig count < 0.005, it can be concluded that simultaneously service quality (x1) and promotion (x2) have a positive effect on consumer purchasing decisions (y) at Indomaret Buana Raya Padang Sambian Denpasar Bali.